ANALISIS PENGARUH KESUKSESAN IMPLEMENTASI CORE BANKING SYSTEM (CBS) DENGAN BERBASIS MODEL DELONE DAN MCLEAN - Mardiana Andarwati (University of Merdeka Malang, 2016)
AbstractCore Banking System (CBS) is banking application system implementation to improve service customers, but whether the bank knew that CBS was categorized applied successfully or not.The purpose of theseresearch are determine the successful implementation of CBS using models DeLone and Mclean IS Success consisting of six variables are system quality , information quality, usage , user satisfaction , individual impact , and impact organizations. Test the hypothesis using the Partial Least Suare (PLS).The results of this study are the quality of the system on the intensity of use and user satisfaction are positive and significant,the quality of information on the intensity of use is positive and significant and then user satisfaction isnegative and not significant, the influence of the intensity of use of the employment impacts of individual positive and significant, user satisfaction to the impact of individual positivel and significant, the intensity of use of the user satisfaction the positive and significant, and the impact individual on the impact of the organizationis positive and significant. So, as to impact individual the best relationship of the impact organization